RESPECT FOR PRIVACY AND PERSONAL DATA PROTECTION IN THE CONTEXT OF MASS SURVEILLANCE OF COMMUNICATION (Journal of the Spanish Institute for Strategic Studies, 2018)
The information leaked by Edward Snowden on the use by the United States and the United Kingdom of technologies that allow the indiscriminate collection of large amounts of data communications has caused great concern across Europe and has opened a debate on the impact of programmes of mass surveillance of communications on human rights. According to the case law of the European Court of Human Rights (ECtHR), such activities are an interference with the private lives of thousands of European citizens. This article analyses the guarantees that Article 8 of the European Convention on Human Rights (ECHR) provides for such interference and assesses whether these safeguards are sufficient in the case of extraterritorial surveillance. It also questions whether the Member States of the Convention are obliged to take measures to protect their citizens against surveillance contrary to the requirements